Analisis Tata Kelola Arsip Dinamis Kantor Kelurahan Cipadung Kecamatan Cibiru Dalam Mewujudkan Kebijakan Tertib Arsip - Nurul Evany; Ratna Dieva Audya; Riza Amalia (UIN Sunan Gunung Djati Bandung, 2023)
Basically, an orderly archive policy, especially regarding dynamic archive management, has been made by the central government as a guide to build awareness of all elements of society on the importance of managing records, especially within the government bureaucracy. Therefore, this study aims to find out how dynamic archives are managed, influencing factors and obstacles in managing dynamic archives in Cipadung Village, Cibiru District. This research uses a descriptive method with a qualitative approach. Observations include the creation, use and maintenance, depreciation of archives, influencing factors and obstacles in managing records. The data analyzed are the results of observations and interviews with the secretary of the lurah and the social welfare section. The results of the study show that the management of dynamic archives in Cipadung Village, Cibiru District is said to be quite good, covering aspects of creation, use, maintenance. Meanwhile, the depreciation aspect needs further attention by the Cipadung Village. In addition, there are factors that influence the management of dynamic archives in the Cipadung Village, namely storage systems and archival facilities. Then, there are obstacles in managing dynamic archives in the Cipadung sub-district, namely the absence of a special room for archives and the inadequacy of Human Resources specifically managing archives